Dear Wise Men. (Journal of Parents and Teachers, 2014)
Christmas is a time to give gifts and gifts. This article proposes a series of ideas to ask in the letter of the Three Wise Men: gifts for oneself, for others and for sharing.
Keywords: Christmas; gifts; Three Wise Men; gift ideas.